2018
DOI: 10.3390/toxins10100393
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Cross-Reactivity in Antivenom Research

Abstract: Antivenom cross-reactivity has been investigated for decades to determine which antivenoms can be used to treat snakebite envenomings from different snake species. Traditionally, the methods used for analyzing cross-reactivity have been immunodiffusion, immunoblotting, enzyme-linked immunosorbent assay (ELISA), enzymatic assays, and in vivo neutralization studies. In recent years, new methods for determination of cross-reactivity have emerged, including surface plasmon resonance, antivenomics, and high-density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 102 publications
(162 reference statements)
1
28
0
Order By: Relevance
“…The antibody developer may piggy-back on the many scientific and technological achievements from the fields of oncology and autoimmune diseases [85], which can be exploited to reap the many technologically low-hanging fruits that exist in the field of neglected tropical diseases due to the lack of prior art. This creates an opportunity for the academic scientist who is evaluated more on his or her ability to perform and publish high impact science than on his or her ability to areas such as understanding and designing cross-reactivity for monoclonal antibodies [107], use of oligoclonal antibody cocktails for multi-target neutralization [1,17,108], novel immunization approaches [109], targeting of evasive pathogens [9,10], and exploitation of novel therapeutic mechanisms of action [41]. Such potential developments will likely be further catalyzed by advances in antibody production technologies that may enable low cost of antibody manufacture [17,110] PDB IDs were obtained from the Protein Data Bank (https://www.rcsb.org).…”
Section: Expert Opinionmentioning
confidence: 99%
“…The antibody developer may piggy-back on the many scientific and technological achievements from the fields of oncology and autoimmune diseases [85], which can be exploited to reap the many technologically low-hanging fruits that exist in the field of neglected tropical diseases due to the lack of prior art. This creates an opportunity for the academic scientist who is evaluated more on his or her ability to perform and publish high impact science than on his or her ability to areas such as understanding and designing cross-reactivity for monoclonal antibodies [107], use of oligoclonal antibody cocktails for multi-target neutralization [1,17,108], novel immunization approaches [109], targeting of evasive pathogens [9,10], and exploitation of novel therapeutic mechanisms of action [41]. Such potential developments will likely be further catalyzed by advances in antibody production technologies that may enable low cost of antibody manufacture [17,110] PDB IDs were obtained from the Protein Data Bank (https://www.rcsb.org).…”
Section: Expert Opinionmentioning
confidence: 99%
“…Localizing the immunogenic region of toxins may allow for the synthesis of small peptides that could be used as synthetic epitopes for immunization. Generally, neutralizing antibodies target epitopes that are three-dimensional structures that may contain discontinuous epitopic elements [ 213 ]. However, some continuous epitopic elements are still able to raise a protective immune response, as extensively exemplified by the studies reported in Table 1 , Table 2 and Table 3 .…”
Section: Biochemical Bioinformatic and Omics Tools That Could Aimentioning
confidence: 99%
“…Toxicovenomics is a proteomicsbased approach that can be used to analyze snake venoms to provide an overview of which toxins are medically relevant in envenomings, and this approach shows promise for selecting the most effective venom mixtures for immunization [7][8][9]. However, toxicovenomics needs to be combined with complementary analytical approaches, such as animal-based neutralization assays, immunochemical studies [3], and antivenomics [10]; these, together, can provide an in-depth view into the molecular reactivity and potential neutralization of these medically relevant toxins [11,12]. Nevertheless, all of these approaches fail to provide information about the specific binding interactions between venom toxin epitopes and antivenom antibody paratopes [11].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, all of these approaches fail to provide information about the specific binding interactions between venom toxin epitopes and antivenom antibody paratopes [11]. Such molecular interaction information is key towards developing a better understanding of the nature of antivenom cross-reactivity and para-specificity and, consequently, the development of improved and broadly neutralizing antivenoms [11,12].…”
Section: Introductionmentioning
confidence: 99%